Linux basics for hackers : getting started with networking, scripting, and security in Kali - OccupyTheWeb (San Francisco : No Starch Press, Inc., 2018)
"Builds a foundation of Linux skills; this guide also addresses MySQL, postgresql, and Python scripting. Provides access to numerous real-world examples and hands-on exercises"--
Getting started with the basics -- Text manipulation -- Analyzing and managing networks -- Adding and removing software -- Controlling file and directory permissions -- Process management -- Managing user environment variables -- Bash scripting -- Compressing and archiving -- Filesystem and storage device management -- The logging system -- Using and abusing services -- Security and anonymity -- Wireless networking -- Linux kernel and drivers -- Scheduling jobs -- Python scripting basics.
Keywords: Kali Linux; Penetration testing (Computer security); Hackers; Operating systems (Computers)